The Terms Postmodernism, Postcoloniality and Postfeminism in the American Literature - Bozorova Viloyat Muzaffarovna (International Journal on Integrated Education, 2022)
The terms postmodernism, postcoloniality and postfeminism in the American literature, insistently pointing to the realm beyond, only embody the restless and constantly redefining energy of modernity, transforming the present into an expanding and eccentric field of experience and power. Being on the other side is being in between. But being on the other side also belongs to the time of rethinking, returning to the present in order to describe anew cultural modernity, to affirm the human and historical community, in order to touch the future of the literature.